SIMULASI PENYESUAIAN BEBAN PADA TRANSFORMATOR DI GARDU INDUK NUSA DUA - Eko Adi Setiawan, I Made; Rinas, I Wayan; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 7 No 2 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i02.p3, 2020)
The rapid development in the South Kuta region has resulted in an increase in the demand for electricity energy that must be supplied by the 150 kV Nusa Dua substation. An increase in the amount of load results in an increase in the load that must be borne by the transformer. To prevent losses due to overload, a load adjustment simulation is performed on the transformer at the Nusa Dua Substation. Load flow simulation is done using ETAP software with the subject of the power transformer load along with the load-feeders. The purpose of the simulation is to know the loading conditions and power loss of the Nusa Dua substation system. Furthermore, the transformer load adjustment scenario is designed, then simulated again with ETAP software to determine changes in the loading conditions and the power loss in the Nusa Dua substation system. Simulation results in existing condition with normal operation, transformer 1 load is 69,8% and transformer 3 is 71,8% with a total power loss of 14,1%. After 3 planning scenarios for transformer load adjustment, scenario 2 is the bestl scenario in short term with the loading on transformer 1 is 50,4%, transformer 2 is 45,9%, and transformer 3 is 45,1% with total power loss of 9,16%. While for the long term, scenario 3 is recommended by adding a new transformer unit. Transformer 1 loading is 50,9%, transformer 2 is 45,9%, and transformer 3 is 45,1% with a total power loss of 9,24%.